Case report: Avoiding intolerance to antipsychotics through a personalized treatment approach based on pharmacogenetics - Korošec Hudnik, Liam; Blagus, Tanja; Redenšek Trampuž, Sara; Dolžan, Vita; Bon, Jurij; Pjevac, Milica (Frontiers in Psychiatry, 2024)
The standard approach to treatment in psychiatry is known as "Treatment-As-Usual" (TAU), in which the same types of treatment are administered to a group of pa ents. TAU o en requires numerous dose adjustments and medica on changes due to ineffec veness and/or the occurrence of adverse drug reac ons (ADR). This process is not only meconsuming but also costly. An psycho c medica ons are commonly used to treat various psychiatric disorders such as schizophrenia, mood disorders and others. Some of the interindividual differences in efficacy and ADR observed in psychopharmacotherapy can be explained by gene c variability in the pharmacokine cs and pharmacodynamics of an psycho cs. A be er understanding of (in)efficacy and possible ADR can be achieved by pharmacogene c analysis of genes involved in the metabolism of an psycho cs. Most psychotropic drugs are metabolized by gene cally variable CYP2D6, CYP1A2, CYP3A4 and CYP2C19 enzymes. To demonstrate the u lity of pharmacogene c tes ng for tailoring an psycho c treatment, in this paper we present the case of a pa ent in whom a pharmacogene c approach remarkably altered an otherwise intolerant or ineffec ve conven onal TAU with an psycho cs.Methods: In this case report, we present a 60-year-old pa ent with psycho c symptoms who suffered from severe extrapyramidal symptoms and a malignant neurolep c syndrome during treatment with risperidone, fluphenazine, aripiprazole, brexpiprazole and olanzapine. Therefore, we performed a pharmacogene c analysis by genotyping common func onal variants in genes involved in the pharmacokine c pathways of prescribed an psycho cs, namely CYP2D6, CYP3A4, CYP3A5, CYP1A2, ABCB1 and ABCG2. Treatment recommenda ons for drug-gene pairs were made according to available evidence-based pharmacogene c recommenda ons from the Dutch Pharmacogenomic Working Group (DPWG) or The Clinical Pharmacogene cs Implementa on Consor um (CPIC).